RENDAHNYA ETIKA PESERTA DIDIK DI ERA MODERNISASI DALAM PANDANGAN AGAMA HINDU - Wirahadi Kusuma, I Made; Wardana, Kadek Agus (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Ethics is a case study that needs to be discussed and advanced lately by us and all the educated categories. Education that teaches children to grow up develops ethics from an early age to adulthood. However, the age of ethical globalization has been declining in some cases, which must be an increasingly sophisticated ethical education of children undergoing an increase. The decrease in ethics in the context of globalization is as severe as the effects of the modernization of state-of-the-art devices through smart phones, as well as the effect of the lack of supervision from the elderly. Almost all of the big cities are experiencing this, so the moral and ethical aspects of children belonging to them who are still active in school need to be evaluated by the government, schools, and parents concerned. This paper aims to give a general picture of the negative influence of increasingly rigid globalization on the children of the students. In Hinduism, the ethics of all human beings, which encompasses the human being, is embedded in the teachings of the Tri Hita Karana itself. The same is true of the concept of